The Analysis Study of Association of Cigarette Smoking and Dry Eye Disease : A Comprehensive Systematic Review - Anindi Putri Harjanti; Indrawati (The International Journal of Medical Science and Health Research, 2024)
Background: Dry eye disease prevalence is significantly influenced by smoking, with cigarette smoke contributing to over seven million deaths annually. Despite the widespread use of electronic cigarettes, public awareness remains limited, and debates persist regarding their safety and long-term health implications, highlighting the urgent need for improved health measures. Methods: This systematic review complied with the PRISMA 2020 requirements, concentrating solely on full-text papers published in English from 2014 to 2024. Editorials and review articles lacking a DOI were omitted to guarantee the use of high-quality sources. A comprehensive literature review was performed using esteemed databases such as ScienceDirect, PubMed, and SagePub to locate pertinent studies. Result: An initial database search identified more than 60 publications relevant to the topic. Following a meticulous three-stage screening process, eight studies were ultimately selected based on predefined inclusion criteria and deemed appropriate for in-depth analysis. These studies underwent a thorough critical appraisal to ensure their quality and relevance, providing a solid foundation for a comprehensive investigation into the association between cigarette smoking and dry eye disease. Conclusion: DED, a common ophthalmology condition, is often underdiagnosed due to its nonspecific symptoms and variability in diagnostic approaches. Cigarette smoke causes lipid peroxidation, tear film instability, and ocular surface damage, impairing epithelial differentiation.